CoNiCrW series high-entropy alloy-based composite material as well as preparation method and application thereof

By combining CoNiCrW-based high-entropy alloy with carbide ceramics, composite materials with high tensile strength and toughness were prepared, which solved the problem of insufficient temperature bearing capacity of existing nickel-based high-temperature alloys in high-temperature environments and was suitable for high-temperature components. application.

CN119120995AActive Publication Date: 2024-12-13AVIC BEIJING INST OF AERONAUTICAL MATERIALS

Patent Information

Application Number
CN202411218091.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2024-12-13
Estimated Expiration
2044-09-02

AI Technical Summary

Technical Problem

The existing nickel-based high-temperature alloys lack the temperature bearing capacity in high-temperature environments, making it difficult to meet the strict requirements for high-temperature components in the fields of aerospace, especially the long-term operating temperature exceeding 1273K.

Method used

CoNiCrW-based high-entropy alloy is used as the matrix, and the composite material is prepared through an additive manufacturing process by combining carbide ceramic powder. The particle size and content of alloy composition and carbide ceramic are adjusted to form a stable interface layer to improve compatibility and tensile strength. .

Benefits of technology

It significantly improves the temperature resistance and mechanical properties of the composite material, can maintain high tensile strength and toughness at temperatures of 1273K and above, and is suitable for high-temperature components such as combustion chamber flame cylinder diffuser components and aerospace fuel injection support plates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119120995A_ABST
    Figure CN119120995A_ABST
Patent Text Reader

Abstract

The invention relates to a CoNiCrW-series high-entropy alloy-based composite material and a preparation method and application thereof, and belongs to the technical field of composite material preparation. The composite material comprises a CoNiCrW-series high-entropy alloy and carbide ceramic, wherein the CoNiCrW-series high-entropy alloy comprises 0.07-0.13% of C, 0.07-0.13% of C, 0.07-0.13% of Cr: 20.5%-23.5%; the content of Ni is 19.5 to 23.0 percent; 16.1% to 18.1% of W; 0.6% to 1.2% of Mn; 0.04% to 0.10% of La; 0.005 to 0.012 percent of B; 0.2 to 0.5 percent of Si; fe < = 2.5%; p is less than 0.002%; s is less than 0.002%; less than 0.0005% of Ag; bi < = 0.0001%; less than 0.0005% of Pb; less than 0.01% of Cu; co: the balance. The obtained composite material has high temperature resistance and strength, and can be used in a high-temperature environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of high entropy alloy component design and composite material preparation, and in particular to a CoNiCrW series high entropy alloy-based composite material and a preparation method and application thereof. Background Art

[0002] With the continuous development of aerospace technology, the requirements for the comprehensive performance of components have been significantly improved due to the more stringent working environment, especially the temperature-bearing capacity of materials. For example, high-temperature components such as the combustion chamber flame tube diffuser assembly of aircraft engines, the wear-resistant layer of turbine blades, the rear support plate of the load-bearing casing, and the injection support plate for aerospace use.

[0003] At present, nickel-based high-temperature alloys are widely used to manufacture high-temperature components. The long-term working temperature of traditional nickel-based high-temperature alloys (such as GH3625, GH3536, GH3230, etc.) is generally limited to 1173K~1253K, and its high-temperature performance faces obvious deficiencies, which seriously restricts the safety and reliability of existing components. It is urgent to develop a new generation of ultra-high temperature structural materials with higher temperature bearing capacity, and the development of new materials with long-term working temperatures above 1273K has broad application prospects. Cobalt-based high-temperature alloy GH5188 is the alloy with the highest heat resistance among traditional deformable high-temperature alloys, and its long-term service temperature can be close to 1273K.

[0004] However, with the continuous increase of turbine pre-temperature and thrust-to-weight ratio, higher temperature-bearing capacity requirements are placed on high-temperature components. It is urgent to develop a new generation of ultra-high temperature structural materials with higher temperature-bearing capacity and develop long-term operating temperatures above 1273K. Summary of the invention

[0005] In view of the above analysis, the present invention aims to provide a CoNiCrW series high entropy alloy-based composite material and a preparation method and application thereof, so as to solve the problem of poor temperature resistance of existing materials.

[0006] On the one hand, the present invention provides a CoNiCrW series high entropy alloy-based composite material, the preparation raw materials include CoNiCrW series high entropy alloy powder and carbide ceramic powder;

[0007] The chemical composition of the CoNiCrW series high entropy alloy, calculated by mass percentage, includes C: 0.07-0.13%; Cr: 20.5-23.5%; Ni: 19.5-23.0%; W: 16.1-18.1%; Mn: 0.6-1.2%; La: 0.04-0.10%; B: 0.005-0.012%; Si: 0.2-0.5%; Fe≤2.5%; P<0.002%; S<0.002%; Ag<0.0005%; Bi≤0.0001%; ​​Pb<0.0005%; Cu<0.01%, Co: balance.

[0008] Furthermore, the chemical composition of the CoNiCrW series high entropy alloy includes, by mass percentage, C: 0.09-0.11%; Cr: 21.5-22.5%; Ni: 20.5-22.0%; W: 17.1-18.1%; Mn: 0.8-1.0%; La: 0.06-0.08%; B: 0.007-0.010%; Si: 0.3-0.4%; Fe≤2.5%; P<0.002%; S<0.002%; Ag<0.0005%; Bi≤0.0001%; ​​Pb<0.0005%; Cu<0.01%, Co: balance.

[0009] Furthermore, the particle size of the CoNiCrW-based high entropy alloy powder is 40 to 90 microns.

[0010] Furthermore, the particle size of the carbide ceramic powder is 40 to 80 microns.

[0011] Furthermore, the carbide ceramic powder is TiC, HfC or NbC.

[0012] Furthermore, the volume content of carbide ceramic powder added to the composite material is in the range of 5 vol.% to 22 vol.%.

[0013] Furthermore, the carbide ceramic powder is dispersed in the composite material.

[0014] On the other hand, the present invention provides a method for preparing the CoNiCrW series high entropy alloy-based composite material, firstly mixing carbide ceramic powder with CoNiCrW series high entropy alloy powder, and then preparing it through an additive manufacturing process to obtain the CoNiCrW series high entropy alloy-based composite material.

[0015] In a third aspect, the present invention provides an application of the CoNiCrW series high entropy alloy-based composite material in a high-temperature component, wherein the high-temperature component has a temperature resistance of above 1100°C.

[0016] Furthermore, the high-temperature components include a combustion chamber flame tube diffuser assembly of an aircraft engine, a turbine blade wear-resistant layer, a load-bearing casing rear support plate, and an aerospace fuel injection support plate.

[0017] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0018] 1. The present invention adjusts and controls the composition ratio of CoNiCrW series high entropy alloy, uses it as a matrix, and then adds carbide ceramics as a reinforcement phase. Under the cooperation of CoNiCrW series high entropy alloy and carbide ceramics, the obtained composite material has high temperature resistance and high performance, and can meet the use in a high temperature environment; the obtained composite material has high tensile strength and toughness. After performance testing, the hardness at room temperature is above 36.7HRC; at 1273K, the tensile strength is above 191MPa, and at 1373K, the tensile strength is above 118MPa;

[0019] 2. In the present invention, after the CoNiCrW series high entropy alloy powder and the carbide ceramic powder are melted by additive manufacturing, the W element in the CoNiCrW series high entropy alloy powder quickly diffuses to the surface of the carbide ceramic and forms a thin interface layer, which can ensure the interface bonding force between the CoNiCrW series high entropy alloy matrix and the carbide ceramic phase, thereby improving the compatibility between the CoNiCrW series high entropy alloy and the carbide ceramic, effectively reducing the risk of interface cracking, and greatly improving the internal metallurgical quality of the composite material and the product.

[0020] 3. The W content in the CoNiCrW high entropy alloy of the present invention is 16.1wt.%-18.1wt.%, a part of the W reacts with the carbide ceramic, and the other part is preserved in the alloy substrate after material addition, thereby ensuring the high temperature resistance of the alloy substrate.

[0021] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0023] Figure 1 Schematic diagram of TiC powder;

[0024] Figure 2 Schematic diagram of CoNiCrW high entropy alloy spherical powder;

[0025] Figure 3 This is a scanning electron microscope image of the microstructure of TiC ceramic reinforced composite materials;

[0026] Figure 4 This is a dark-field transmission electron microscope photograph of the microstructure of TiC ceramic reinforced composite materials. DETAILED DESCRIPTION

[0027] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0028] With the continuous development of aerospace, the requirements for its manufacturing parts are getting higher and higher, especially for heat-resistant parts. At present, heat-resistant parts mostly use traditional nickel-based high-temperature alloys, such as GH3625, GH3536, and GH3230, and the long-term working temperature is generally limited to 1173K~1253K. With continuous research, a cobalt-based high-temperature alloy with the grade GH5188 was developed. It is the alloy with the highest heat resistance among traditional deformation high-temperature alloys, and its long-term service temperature can be close to 1273K.

[0029] However, with the continuous increase in the temperature before the turbine and the thrust-to-weight ratio, higher temperature-bearing capacity requirements are placed on temperature-resistant components. Therefore, a material that can operate at a temperature above 1273K for a long time is needed.

[0030] The present invention provides a CoNiCrW series high entropy alloy-based composite material, wherein the raw materials for preparing the composite material include CoNiCrW series high entropy alloy powder and carbide ceramic powder;

[0031] The chemical composition of the CoNiCrW series high entropy alloy, calculated by mass percentage, includes C: 0.07-0.13%; Cr: 20.5-23.5%; Ni: 19.5-23.0%; W: 16.1-18.1%; Mn: 0.6-1.2%; La: 0.04-0.10%; B: 0.005-0.012%; Si: 0.2-0.5%; Fe≤2.5%; P<0.002%; S<0.002%; Ag<0.0005%; Bi≤0.0001%; ​​Pb<0.0005%; Cu<0.01%, Co: balance.

[0032] Compared with the prior art, the composite material provided by the present invention is based on a CoNiCrW series high entropy alloy as a matrix, and carbide ceramics are added as a reinforcement phase. Through the mutual cooperation of the two, the temperature resistance of the composite material can be improved, and it can be stably used in a temperature environment of 1100°C and above.

[0033] The CoNiCrW alloy provided in the present invention is a cobalt-based alloy. The mixing entropy value of the alloy can be changed by changing the elements. The mixing entropy value exceeds 1.5R, meets the requirements of high entropy alloys, and is easier to form a solid solution, so that the matrix and the composite material have better stability at high temperatures. The CoNiCrW alloy produces a lattice distortion effect in the structure and a delayed diffusion effect in the kinetics, so that the alloy matrix is ​​strengthened and is conducive to the generation of submicron precipitation phases, thereby achieving the improvement of the temperature bearing capacity and mechanical properties of the composite material.

[0034] The present invention strictly controls the chemical composition ratio in the CoNiCrW alloy, especially the W element content is 16.1-18.1%. The W element has an important influence on the high temperature performance of the CoNiCrW alloy, and can significantly improve the high temperature strength of the alloy. First, there is the solid solution strengthening effect. The W element will form a stable solid solution in the alloy lattice. Even at high temperatures, it can hinder the slip and dislocation movement of the lattice, thereby improving the deformation resistance and strength of the alloy; second, there is the precipitation strengthening effect. The W element helps to form a small and uniform precipitation phase, especially under high temperature conditions. These precipitation phases can exist stably and hinder the movement of dislocations and the slip of grains, effectively enhancing the high temperature strength of the alloy; third, there is the grain boundary strengthening effect. The W element can change the grain boundary structure of the alloy and increase the strength of the grain boundary. The strengthened grain boundary can effectively prevent the movement of the grain boundary and the growth of the grain, maintain the microstructural stability of the alloy at high temperatures, thereby improving the high temperature strength and performance of the alloy and the composite material.

[0035] The W element in the CoNiCrW alloy diffuses. Under the action of the additive manufacturing process, a W-containing interface layer can be formed on the surface of the carbide ceramic, which can improve the bonding force between the CoNiCrW alloy matrix and the carbide ceramic and ensure the overall performance of the composite material. However, when the W element content is below 16.1%, the W element in the CoNiCrW alloy diffuses, resulting in a decrease in the W content in the matrix, thereby reducing the heat resistance or high temperature strength of the composite material; when the W element content is above 18.1%, harmful phases will be generated, ultimately leading to a decrease in the overall performance of the composite material.

[0036] The main functions of other elements in the CoNiCrW high entropy alloy of the present invention are as follows:

[0037] Co element: Co element in this alloy is a matrix element, mainly as a solid solution strengthening element of high entropy alloy, which can enhance the strength and heat resistance of high entropy alloy. In addition, Co element can also improve the high temperature plasticity and toughness of high entropy alloy, and improve the high temperature deformation ability of high entropy alloy.

[0038] Cr element: Cr element is mainly used to improve the oxidation resistance and corrosion resistance of high entropy alloys. Chromium can form a dense oxide film layer to prevent oxygen and other corrosive media from corroding the alloy, while improving the high-temperature oxidation stability of high entropy alloys.

[0039] Ni element: Ni element can improve the plasticity and toughness of the alloy, and at the same time form a solid solution with other elements to enhance the strength and heat resistance of the high entropy alloy.

[0040] Fe element: Fe element is mainly used to adjust the organization of high entropy alloy and improve its processing performance. Iron forms a solid solution with other elements, and at the same time helps stabilize the lattice structure of high entropy alloy, and improves the strength and heat resistance of high entropy alloy.

[0041] C element: C element is usually used to form carbides to improve the hardness and wear resistance of high entropy alloys. Reasonable control of carbon content can improve the heat treatment process and mechanical properties of high entropy alloys.

[0042] Mn element: Mn element is usually used to improve the cold working performance and hot corrosion resistance of high entropy alloys. Mn element can increase the strength and hardness of high entropy alloys and improve the processing performance of alloys.

[0043] The remaining components in the CoNiCrW series high entropy alloy are all trace elements, among which La element improves the alloy's oxidation resistance and high temperature strength. B element improves the alloy's hardness and strength, and Si element enhances the alloy's oxidation resistance and fluidity. P and Cu elements can improve hardness and strength, and Ag and Bi elements can improve corrosion resistance, but the content must be strictly controlled, otherwise it will seriously affect the alloy's brittleness. S and Pb elements are impurity elements and their content must be strictly controlled.

[0044] The present invention uses CoNiCrW series high entropy alloy as a matrix and adds carbide ceramic as a reinforcement phase to prepare a composite material. Through the interaction of the above elements, the matrix can be guaranteed to have stable performance, thereby ensuring the performance of the obtained composite material.

[0045] Specifically, the chemical composition of the CoNiCrW series high entropy alloy includes, by mass percentage, C: 0.07-0.13%; Cr: 20.5-23.5%; Ni: 19.5-23.0%; W: 16.1-18.1%; Mn: 0.6-1.2%; La: 0.04-0.10%; B: 0.005-0.012%; Si: 0.2-0.5%; Fe≤2.5%; P<0.002%; S<0.002%; Ag<0.0005%; Bi≤0.0001%; ​​Pb<0.0005%; Cu<0.01%; Co: balance.

[0046] Preferably, the chemical composition of the CoNiCrW series high entropy alloy includes, by mass percentage, C: 0.10%; Cr: 22.1%; Ni: 21.5%; W: 17.3%; Mn: 0.95%; La: 0.07%; B: 0.008%; Si: 0.35%; Fe: 2.5%; P: 0.0015%; S: 0.0018%; Ag: 0.0004%; Bi: 0.0001%; ​​Pb: 0.0004%; Cu: 0.005%; Co: balance;

[0047] Specifically, the particle size of the CoNiCrW high entropy alloy powder is 40 to 90 microns.

[0048] Specifically, the particle size of the carbide ceramic powder is 40 to 80 microns.

[0049] It should be noted that in the present invention, the CoNiCrW series high entropy alloy powder is spherical, and its particle size is controlled within the range of 40 to 90 microns; the carbide ceramic powder is quasi-spherical, and its particle size is controlled within the range of 40 to 80 microns. When the particle size is within the above range, the powder particle size is more uniform. There are two main benefits to controlling the particle size of the powder. The first is to ensure the uniformity and consistency of the additive manufacturing process, which is conducive to the layer-by-layer stacking and melting in the additive manufacturing process, and can ensure that the resulting composite material has higher performance and temperature resistance; the second is to ensure the fluidity of the raw materials and the stability of the molten pool. The uniform particle size range makes the powder more fluid in the additive manufacturing equipment and can be evenly stacked, thereby improving the molding quality and surface smoothness. However, when the powder exceeds the above particle size range, it is easy to cause a decrease in the quality of the composite material forming, resulting in uneven stacking or unstable melting quality, which reduces the dimensional accuracy and mechanical properties of the composite material.

[0050] Preferably, the particle size of the CoNiCrW-based high entropy alloy powder is 50 to 80 microns.

[0051] More preferably, the particle size of the CoNiCrW-based high entropy alloy powder is 60 to 70 microns.

[0052] Preferably, the particle size of the carbide ceramic powder is 50 to 70 microns.

[0053] More preferably, the particle size of the carbide ceramic powder is 60 to 65 microns.

[0054] Specifically, the carbide ceramic powder includes TiC, HfC or NbC.

[0055] It should be noted that the three carbides TiC, HfC and NbC have good chemical stability and compatibility. Their melting points are as high as 3200℃ (TiC), 3890℃ (HfC) and 3180℃ (NbC), respectively. They have good chemical stability and compatibility with other alloy elements at high temperatures. They can form stable compounds and phases with elements in high entropy alloys (such as Co, Ni, Cr, etc.), are not easy to decompose or react at high temperatures, and help maintain the stability and performance of composite materials. In addition, TiC, HfC and NbC have good hardness and wear resistance, and can effectively protect the alloy matrix under high temperature and high stress environment, and extend the service life of composite materials or parts. In addition, the thermal conductivity and thermal expansion coefficient of TiC, HfC and NbC are similar to those of CoNiCrW series high entropy alloys, which is beneficial to reduce the stress, deformation and even cracks caused by thermal expansion mismatch between the matrix and the ceramic reinforcement phase, thereby improving the stability and reliability of the composite material.

[0056] The carbide ceramic powder of the present invention does not contain carbides such as WC. Although it also has good hardness and wear resistance, WC has poor compatibility with the CoNiCrW series high entropy alloy matrix, which will cause adverse chemical reactions or interactions in the matrix, resulting in instability or performance degradation of the composite material. At the same time, the thermal expansion coefficient of WC may not match that of the high-temperature alloy matrix, which may cause cracks or interface peeling problems during thermal cycles, reducing the strength of the composite material.

[0057] Specifically, the volume content of the carbide ceramic powder added to the composite material is in the range of 5 vol.% to 22 vol.%.

[0058] It should be noted that the present invention uses carbide ceramics as a reinforcing phase and a CoNiCrW series high entropy alloy as a metal matrix. The composite material is prepared by reinforcing the CoNiCrW series high entropy alloy with carbide ceramics. The carbide ceramics and the elements in the high entropy alloy (such as Co, Ni, Cr, etc.) can form stable compounds and phases, and the obtained composite material has high temperature resistance and mechanical properties as a whole.

[0059] In the present invention, it is necessary to control the amount of carbide ceramic powder added, and the content is controlled at 5vol.% to 22vol.%, and the overall effect of the obtained composite material is better. When the content of carbide ceramic powder is lower than 5vol.%, the carbide ceramic content is too low to play a reinforcing role, and the strength of the composite material is not significantly improved; when the content of carbide ceramic powder is higher than 22vol.%, the ceramic content is too high and the brittleness increases rapidly, and the composite material cannot eliminate cracks and is difficult to form. The content of carbide ceramic powder in the present invention can be 5vol.%, 8vol.%, 10vol.%, 13vol.%, 15vol.%, 18vol.%, 20vol.% or 22vol.%.

[0060] Preferably, the content of the carbide ceramic powder is 8 vol.%-20 vol.%.

[0061] More preferably, the content of the carbide ceramic powder is 10 vol.%-18 vol.%.

[0062] Specifically, the carbide ceramic powder is dispersed in the composite material.

[0063] It should be noted that dispersed distribution can make carbides evenly distributed in the matrix material, ensure the consistency of the composite material performance, and avoid the situation where the performance of local areas is too low or too high. Carbides dispersed in the composite material can effectively hinder the expansion of cracks, thereby enhancing the strength and toughness of the composite material and improving the overall tensile and compressive properties.

[0064] The invention provides a method for preparing a CoNiCrW series high entropy alloy-based composite material. Carbide ceramic powder and CoNiCrW series high entropy alloy powder are firstly mixed, and then the mixture is prepared by an additive manufacturing process to obtain the CoNiCrW series high entropy alloy-based composite material.

[0065] Compared with the prior art, the present invention weighs carbide ceramic powder and CoNiCrW series high entropy alloy powder according to corresponding volume ratios, then mixes the two, and then adopts an additive manufacturing process to melt and prepare a composite material.

[0066] The present invention generates a uniformly distributed fine carbide ceramic reinforcement phase in the composite material through an additive manufacturing process. The dispersed carbide ceramic has a good strengthening effect on the high-temperature strength of the composite material, and there are no defects such as micro cracks and holes inside the composite material. In addition, through the additive manufacturing process, the W element in the CoNiCrW series high entropy alloy quickly diffuses to the surface of the carbide ceramic and forms a thin interface layer to ensure the interface bonding force between the CoNiCrW series high entropy alloy matrix and the carbide ceramic phase, thereby improving the compatibility between the CoNiCrW series high entropy alloy matrix and the carbide ceramic, effectively reducing the risk of interface cracking, greatly improving the internal metallurgical quality of the composite material, and being able to prepare large-sized temperature-resistant parts.

[0067] Specifically, the surface of the carbide ceramic phase has an interface layer, and the interface layer is a tungsten-containing interface.

[0068] Specifically, the interface layer comprises a (Ti, W)C compound and has a thickness of 50 to 200 nm.

[0069] It should be noted that the thickness of the interface layer is mainly affected by the particle size of the original ceramic powder. In order to ensure the fluidity of the powder, the particle size of the selected ceramic powder is 40-80 microns, so the thickness of the interface layer is controlled at 50-200nm. The larger the particle size of the original ceramic powder, the thicker the corresponding interface layer.

[0070] Preferably, the thickness of the interface layer is 50-200 nm.

[0071] Specifically, the additive manufacturing is a laser selective melting process, a laser melting deposition process or an electron beam selective melting process.

[0072] When the additive manufacturing is a laser selective melting process, the power of the laser selective melting is 250-300W, the scanning speed is 1000-1100mm / s, the scanning spacing is 0.11mm, and the layer thickness is 50μm;

[0073] When the additive manufacturing is a laser melting deposition process, it includes both single-channel and dual-channel methods. The powder feeding amount of the powder feeding channel is 1600rpm-2000rpm, and the powder carrier gas flow rate is 6L / min-8L / min; the laser power is 700-800W, and the scanning speed is 600-700mm / min;

[0074] When additive manufacturing is an electron beam selective melting process, the vacuum degree is 2×10 -3 ±0.5×10 -4 mbar, the working voltage is 60kV, the electron beam power is set to 5000-5500W, the thickness of each powder layer is 50μm, and the preheating temperature is 500-600℃.

[0075] Specifically, the CoNiCrW series high entropy alloy-based composite material provided by the present invention can be used in high-temperature components, and the temperature resistance of the high-temperature components is above 1100° C. The high-temperature components include the combustion chamber flame tube diffuser assembly of the aircraft engine, the load-bearing casing rear support plate and the aerospace fuel injection support plate.

[0076] In order to more clearly describe the present invention, the following examples and comparative examples are provided. Figure 1-4 Further explanation.

[0077] Example 1

[0078] Preparation of CoNiCrW high entropy alloy-based composite materials: comprising the following steps:

[0079] S1: CoNiCrW series high entropy alloy powder and carbide ceramic powder are mixed according to corresponding volume ratios, wherein the carbide ceramic powder accounts for 15 vol.% of the total volume; the CoNiCrW series high entropy alloy powder is spherical, and its particle size is controlled within the range of 60 microns; the carbide ceramic powder is quasi-spherical, and its particle size is controlled within the range of 60 microns;

[0080] The chemical composition of CoNiCrW high entropy alloy is C: 0.10%; Cr: 22.1%; Ni: 21.5%; W: 17.3%; Mn: 0.95%; La: 0.07%; B: 0.008%; Si: 0.35%; Fe: 2.5%; P: 0.0015%; S: 0.0018%; Ag: 0.0004%; Bi: 0.0001%; ​​Pb: 0.0004%; Cu: 0.005%; Co: balance;

[0081] The carbide ceramic powder is TiC;

[0082] S2: Spread the mixed powder, and then use laser selective melting for additive manufacturing, the power of the laser selective melting is 280W, the scanning speed is 1000mm / s, the scanning interval is 0.11mm, and the layer thickness is 50μm; obtain a composite material.

[0083] Example 2

[0084] The preparation process of Example 2 is substantially the same as that of Example 1, except that the chemical composition of the CoNiCrW high entropy alloy in Example 2 is C: 0.07%; Cr: 20.5%; Ni: 19.5%; W: 16.1%; Mn: 0.6%; La: 0.04%; B: 0.005%; Si: 0.2%; Fe: 2.5%; P: 0.0015%; S: 0.0018%; Ag: 0.0004%; Bi: 0.0001%; ​​Pb: 0.0004%; Cu: 0.005%; Co: balance;

[0085] Example 3

[0086] The preparation process of Example 3 is substantially the same as that of Example 1, except that the chemical composition of the CoNiCrW high entropy alloy in Example 3 is C: 0.13%; Cr: 23.5%; Ni: 23.0%; W: 18.1%; Mn: 1.2%; La: 0.10%; B: 0.012%; Si: 0.5%; Fe: 2.5%; P: 0.0015%; S: 0.0018%; Ag: 0.0004%; Bi: 0.0001%; ​​Pb: 0.0004%; Cu: 0.005%; Co: balance;

[0087] Examples 4-9, Comparative Examples 1-3

[0088] The preparation processes of Examples 4-9 and Comparative Examples 1-3 are substantially the same as those of Example 1, except for the differences shown in Table 1.

[0089] Table 1 Parameters of Examples 4-9, Comparative Examples 1-3 and Example 1

[0090]

[0091] Comparative Example 4

[0092] The preparation process of Comparative Example 4 is substantially the same as that of Example 1, except that the chemical composition of the CoNiCrW high entropy alloy in Comparative Example 4 is W: 15.1%.

[0093] Comparative Example 5

[0094] The preparation process of Comparative Example 5 is substantially the same as that of Example 1, except that the chemical composition of the CoNiCrW high entropy alloy in Comparative Example 5 is W: 19.1%.

[0095] Comparative Example 6

[0096] The preparation process of Comparative Example 6 is substantially the same as that of Example 1, except that Comparative Example 6 is a cobalt-based high-temperature alloy GH5188 and does not contain carbide ceramics.

[0097] Performance Testing

[0098] The above-mentioned Examples 1-9 and Comparative Examples 1-6 were subjected to performance tests, mainly including tensile strength and elongation at room temperature, high temperature 1273K and 1373K. The test results are shown in Table 2.

[0099] Table 2 Performance test results

[0100]

[0101] It can be seen from Examples 1-9 and Comparative Examples 1-6 and Table 2 that when the technical solutions provided in Examples 1-9 of the present invention are adopted, the obtained composite materials have higher tensile strength and toughness. After performance testing, the hardness at room temperature is above 36.7HRC; at 1273K, the tensile strength is above 191MPa, and at 1373K, the tensile strength is above 118MPa.

[0102] Examples 10-14, Comparative Examples 7-8

[0103] Example 10

[0104] The preparation process of Example 10 is substantially the same as that of Example 1, except that in Example 10, laser selective melting is used for additive manufacturing, the power of the laser selective melting is 250 W, the scanning speed is 1000 mm / s, the scanning spacing is 0.11 mm, and the layer thickness is 50 μm.

[0105] Embodiment 11

[0106] The preparation process of Example 11 is substantially the same as that of Example 1, except that in Example 11, laser selective melting is used for additive manufacturing, the power of the laser selective melting is 300 W, the scanning speed is 1100 mm / s, the scanning spacing is 0.11 mm, and the layer thickness is 50 μm.

[0107] Example 12

[0108] The preparation process of Example 12 is substantially the same as that of Example 1, except that a single-channel powder feeding method is adopted in Example 12, and the mixed powder of CoNiCrW high entropy alloy and TiC is respectively loaded into a powder feeding channel, the powder feeding amount of the powder feeding channel is 2000rpm, and the powder carrier gas flow rate is 7L / min; the power of laser melting deposition is 700W, and the scanning speed is 600mm / min.

[0109] Embodiment 13

[0110] The preparation process of Example 13 is substantially the same as that of Example 1, except that in Example 13, when the additive manufacturing is an electron beam selective melting process, the vacuum degree is 2×10 -3 ±0.5×10 -4mbar, the working voltage is 60kV, the electron beam power is set to 5000W, the thickness of each powder layer is 50μm, and the preheating temperature is 500℃.

[0111] Embodiment 14

[0112] The preparation process of Example 14 is substantially the same as that of Example 1, except that in Example 14, when the additive manufacturing is an electron beam selective melting process, the vacuum degree is 2×10 -3 ±0.5×10 -4 mbar, the working voltage is 60kV, the electron beam power is set to 5500W, the thickness of each powder layer is 50μm, and the preheating temperature is 600℃.

[0113] Comparative Example 7

[0114] The preparation process of Comparative Example 7 is substantially the same as that of Example 1, except that in Comparative Example 7, laser selective melting is used for additive manufacturing, the power of the laser selective melting is 350 W, the scanning speed is 1500 mm / s, the scanning spacing is 0.11 mm, and the layer thickness is 50 μm.

[0115] Comparative Example 8

[0116] The preparation process of Comparative Example 8 is substantially the same as that of Example 1, except that in Comparative Example 8, when the additive manufacturing is an electron beam selective melting process, the vacuum degree is 2×10 -3 ±0.5×10 -4 mbar, the working voltage is 60kV, the electron beam power is set to 6500W, the thickness of each powder layer is 50μm, and the preheating temperature is 750℃.

[0117] Performance Testing

[0118] The above-mentioned Examples 10-14 and Comparative Examples 7-8 were subjected to performance tests, mainly including tensile strength and toughness at room temperature and high temperature at 1273K and 1373K. The test results are shown in Table 3.

[0119] Table 3 Performance test results

[0120]

[0121] It can be seen from Examples 1, 10-14 and Comparative Examples 7-8 and Table 3 that when the method for preparing the composite material provided by the embodiment of the present invention is adopted, the obtained composite material has high tensile strength and toughness. After performance testing, the hardness at room temperature is above 39.7HRC; at 1273K, the tensile strength is above 209MPa, and at 1373K, the tensile strength is above 120MPa.

[0122] Application Examples

[0123] The composite material obtained above is used to prepare temperature-resistant parts, the temperature resistance of the high-temperature parts is above 1100°C, and the high-temperature parts include combustion chamber flame tube diffuser components of aircraft engines, turbine blade wear-resistant layers, load-bearing casing rear support plates and aerospace fuel injection support plates.

[0124] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A CoNiCrW high entropy alloy-based composite material, characterized in that: The preparation raw materials include CoNiCrW series high entropy alloy powder and carbide ceramic powder; The chemical composition of the CoNiCrW series high entropy alloy includes, by mass percentage, C: 0.07-0.13%; Cr: 20.5-23.5%; Ni: 19.5-23.0%; W: 16.1~18.1%; Mn: 0.6~1.2%; La: 0.04~0.10%; B: 0.005~0.012%: Si: 0.2~0.5%; Fe≤2.5%; P<0.002%; S<0.002%; Ag<0.0005%; Bi≤0.0001%; Pb<0.0005%; Cu<0.01%, Co: balance.

2. The CoNiCrW high entropy alloy-based composite material according to claim 1, characterized in that: The chemical composition of the CoNiCrW series high entropy alloy includes, by mass percentage, C: 0.09-0.11%; Cr: 21.5-22.5%; Ni: 20.5-22.0%; W: 17.1~18.1%; Mn: 0.8~1.0%; La: 0.06~0.08%; B: 0.007~0.010%: Si: 0.3~0.4%; Fe≤2.5%; P<0.002%; S<0.002%; Ag<0.0005%; Bi≤0.0001%; Pb<0.0005%; Cu<0.01%, Co: balance.

3. The CoNiCrW high entropy alloy-based composite material according to claim 1 or 2, characterized in that: The particle size of the CoNiCrW high entropy alloy powder is 40 to 90 microns.

4. The CoNiCrW high entropy alloy-based composite material according to claim 1, characterized in that: The particle size of the carbide ceramic powder is 40 to 80 microns.

5. The CoNiCrW high entropy alloy-based composite material according to claim 1, characterized in that: The carbide ceramic powder is TiC, HfC or NbC.

6. The CoNiCrW high entropy alloy-based composite material according to claim 1, characterized in that: The volume content of the carbide ceramic powder added to the composite material is in the range of 5 vol.% to 22 vol.%.

7. The CoNiCrW high entropy alloy-based composite material according to claim 1, characterized in that: The carbide ceramic powder is dispersed in the composite material.

8. A method for preparing a CoNiCrW high entropy alloy-based composite material according to any one of claims 1 to 7, characterized in that: The carbide ceramic powder is first mixed with the CoNiCrW series high entropy alloy powder, and then prepared by an additive manufacturing process to obtain a CoNiCrW series high entropy alloy-based composite material.

9. Use of the CoNiCrW high entropy alloy-based composite material according to any one of claims 1 to 7 in high-temperature components, characterized in that: The high temperature component has a temperature resistance of above 1100°C.

10. The use of the CoNiCrW high entropy alloy-based composite material in high-temperature components according to claim 9, characterized in that: The high-temperature components include a combustion chamber flame tube diffuser assembly, a turbine blade wear-resistant layer, a load-bearing casing rear support plate and an aerospace fuel injection support plate of an aircraft engine.

Citation Information

Patent Citations

  • Base-containing high-entropy alloy composite and preparation method thereof

    CN108504890A

  • High-entropy alloy gradient material and preparation method thereof

    CN113981291A

  • High-entropy reinforced amorphous alloy composite material and preparation method thereof

    CN113981333A

  • High-entropy alloy composite material for additive manufacturing as well as preparation method and application of high-entropy alloy composite material

    CN114951644A

  • Cellular isomeric nano-precipitate high-temperature reinforced high-entropy alloy and preparation method and application thereof

    CN117127083A

Cited By

  • TiC particle reinforced CoNiCrW series high-entropy alloy composite material as well as preparation method and application of TiC particle reinforced CoNiCrW series high-entropy alloy composite material

    CN119243015A